2019
DOI: 10.1177/2332649219854465
|View full text |Cite
|
Sign up to set email alerts
|

Social Class and Educational Attainment: Do Blacks Benefit Less from Increases in Parents’ Social Class Status?

Abstract: Classic and contemporary studies show that greater social class status is associated with higher levels of education for youth. However, racialized processes might constrain the benefits blacks receive from increases in parents’ social class. In this study the authors use the Education Longitudinal Study of 2002 to estimate whether race moderates the relationship among three common measures of youths’ social class during high school (parents’ occupations, family income, and parents’ level of education) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…Compared to non-Hispanic white (NHW) adolescents, racial minority adolescents, particularly non-Hispanic black (NHB) adolescents, are at an increased risk of school dropout and poor academic achievement [1]. As academic success in the earlier stages of life is a gateway to future economic development and health later in life [2][3][4][5], it is imperative to close the racial inequalities early in life if we wish to eliminate subsequent inequalities during adulthood [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to non-Hispanic white (NHW) adolescents, racial minority adolescents, particularly non-Hispanic black (NHB) adolescents, are at an increased risk of school dropout and poor academic achievement [1]. As academic success in the earlier stages of life is a gateway to future economic development and health later in life [2][3][4][5], it is imperative to close the racial inequalities early in life if we wish to eliminate subsequent inequalities during adulthood [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Two-parent White and Black households did not differ in the return of parental education. For adolescents not in two-parent households, however, Blacks and Hispanics benefit less than non-Hispanic Whites from mothers' but not fathers' occupational prestige on their college enrollment [8].…”
Section: Discussionmentioning
confidence: 95%
“…A recent study used some national data and found that Black adolescents receive smaller academic benefits from parental social class than their white counterparts [8]. Authors found that youth from highly educated Black and Hispanic families are less likely to be accepted to college despite high occupational prestige of their parents [8]. They, however, found that parents' gender and parental marital status play a role in the racial differences in the marginal return of parental SES on adolescents' outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Bumpus, Umeh, and Harris [54], Black youth receive smaller benefits from their parents' social class than non-Hispanic Whites. They found that for youth not in married households, Blacks gain less benefits from their mothers' occupational prestige on their youth outcomes (particularly college enrollment) than non-Hispanic Whites [54]. Previous research has shown that these patterns hold for education [3], employment [55], income [19,49,51,56,57], and marital status [58].…”
Section: Discussionmentioning
confidence: 98%